CONDIÇÕES DE TRABALHO E O IMPACTO NA SAÚDE DOS PROFISSIONAIS DE ENFERMAGEM FRENTE A COVID-19 - Fernanda Moura D'Almeida Miranda; Leni de Lima Santana; Aline Cecília Pizzolato; Leila Maria Mansano Sarquis (Universidade Federal do Paraná, 2020)
Objective: To reflect on the working conditions of the nursing professionals when facing the new coronavirus and to point out the impact on the lives of these professionals in the midst of the pandemic. Development: The weaknesses found in the daily work of the nursing professionals are described by the national and international literature, which include poor working conditions, physical, and mental overload, low pay, and lack of adequate Personal Protective Equipment to cope with this condition. Final considerations: This reflection can contribute to rethink the health and safety of the nursing professionals with a view to providing quality and safe care to the patients in the context of this disease.